A Study of Neurodevelopemental Outcome in Hyperbilirubinaemic Neonates Admitted in NICU - Monika Sharma; Gunshyam Singh Sengar; Niranjan Nagaraj; Shikha Khandelwal; Pramod Kumar Berwal; Vikram Yadav (JCDR Research and Publications Pvt. Ltd., 2018)
Introduction: Hyperbilirubinaemia may be toxic to the developing central nervous system and may cause neurological impairment. The developing brain of premature babies is extremely vulnerable to injury. With increased level of bilirubin, the risk for neurodevelopmental deficit increases with decreasing gestational age and birth weight resulting in relatively high risk of cerebral palsy, developmental delay, hearing and vision impairment and subnormal academic achievement. Aim: This study was conducted to identify factors and pattern of abnormal neurodevelopment at three and 12 months in babies having birth weight >1.5 Kg and gestational age >34 weeks with neonatal hyperbilirubinaemia. Materials and Methods: This prospective study was conducted at Sardar Patel Medical College, Bikaner (Rajasthan), India, from 2014 to 2015. Hyperbilirubinaemia in newborns were examined at three month and 12 month age and their neurodevelopmental assessment done by DASI method. All the collected data was tabulated and stastically analysed by using SPSS software. Results: Out of 96, 67 (69.79%) of hyperbilirubinaemic neonates were males and 29 (30.21%) were females. The prevalence of neurodevelopmental abnormalities (DQ=70) was 10.42% at three months where as it was 6.25% at 12 months follow-up. Early onset of jaundice (=1 day), serum bilirubin level >25 mg/dL, duration of hospital stay >3 days and requirement of exchange transfusion was significantly associated with adverse neurodevelopmental outcomes (DQ=70) at three and 12 months of age. Conclusion: This study found a high prevalence of adverse neurodevelopmental outcome in neonates with hyperbilirubinaemia. Early detection of neurodevelopmental abnormalities and initiation of early intervention measures to reduce the prevalence of neurodevelopmental abnormalities in hyperbilirubinaemic neonates.